Cytotoxic, apoptotic, and anti-inflammatory properties of Adenoon indicum leaf methanolic extract using HT29 cell lines (Bangladesh Journal of Pharmacology, 2025)
In the present study, methanolic extract of Adenoon indicum leaves is investigated for its cytotoxic, apoptotic, and anti-inflammatory properties using HT29 cell lines. The extract yield was 1.6%. MTT assay of HT-29 cells shows that the extract's IC50 value was 80 μg/mL with 10 μg/mL for doxorubicin, confirming its cytotoxic effect. Flow cytometry analysis demonstrated that extract caused cell cycle arrest, with 2.3% of cells in the G2/M phase and 32.2% in the S phase at a dosage of 160 μg/mL. Propidium iodide/annexin V staining revealed that the extract caused 3.1% early apoptosis and 6.0% late apoptosis, compared to 0% early apoptosis and 13.4% late apoptosis with doxorubicin at 11 μg/mL and anti-inflammatory effect in the egg albumin denaturation inhibition assay. The results show methanolic extract of A. indicum has anti-cancer activities against colorectal cancer via triggering apoptosis, and cell cycle arrest. In addition, it has an anti-inflammatory effect.